PENGEMBANGAN MEDIA FLASHCARD DIGITAL MATERI SIMBOL-SIMBOL PANCASILA PADA MATA PELAJARAN PPKn - Rifalda Amadea Ardiani; Dinie Anggraeni Dewi; Yayang Furi Furnamasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is a research on the development of learning media “Digital Flashcard” on the material of Pancasila symbols for class II Elementary School which was carried out due to the lack of use of learning media in the process of teaching and learning activities. The purpose of this study was to determine the design, development process and to see the responses of teachers and students in using digital flashcard learning media on the material of Pancasila symbols. This study uses the Design and Development research method using the ADDIE model development which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques were carried out using questionnaires, interviews, and literature studies as a complement. The result of this research is to design a digital flashcard in accordance with the material of Pancasila symbols. Produce digital flashcard media products in the form of web and applications that get assessments from material experts in very feasible criteria and from media experts in very feasible criteria. As well as the response from teachers and students as media users who get scores in very decent criteria. Based on the results of the research, digital flashcard material for Pancasila symbols is very feasible and can be used in the learning process.